The effect of a barley-based food product in alleviating knee osteoarthritis discomfort symptoms in Egyptian female patients - Suzanne Fouad; Rasha Monir; Fatma A. Ibrahim; Ahmed M.S. Hussein; Heba F. Shafei; Aliaa El Gendy (Journal of the Arab Society for Medical Research, 2023)
Background/aim Osteoarthritis is a common joint condition that causes cartilage to erode. There are numerous conventional treatments available, including nonsteroidal anti-inflammatory medicines and pharmaceuticals containing glucosamine; however, taking them can result in serious side effects. The aim of this study was to prepare barley-based food product enriched with ginger, curcumin, garlic powder, and onion powder and to evaluate the effect of consumption of the prepared macaroni for 2 months, in alleviating knee osteoarthritis discomfort symptoms in female patients complaining of grade 2–3 knee osteoarthritis. Patients and methods The present study enrolled 51 Egyptian middle age females patients with a mean age of 51±8.37 years, diagnosed with bilateral grade two to three knee osteoarthritis were recruited from the National Research Centre rheumatology and rehabilitation clinic. Anthropometric measurements and blood samples were collected after 8 weeks of daily barley based macaroni supplementation (75 grams raw). Serum levels of IL1β, IL4 and IL6 were measured using Elisa techniques, while Total Antioxidant Capacity, Malondialdehyde, and Glutathione S-transferase were measured by the colorimetric methods. Results Chemical composition analysis of the prepared barley-based macaroni demonstrated a decrease in total carbohydrate content and an increase in crude fiber, protein, and fat content compared with the control (semolina wheat-based macaroni); 100 grams of the prepared uncooked barley macaroni provided 342.46 Kcal. The reevaluation of the anthropometric parameters after 8 weeks of daily macaroni supplementation denoting improvement without statistical significance (P>0.05), and the clinical characteristics of knee joint osteoarthritis (Lequesne Index, WOMAC score, and Timed Up and Go test) significantly improved which meant less pain and stiffness. The serum pro-inflammatory cytokines IL1β and IL6 declined significantly and the serum anti-inflammatory cytokine IL4 raised significantly (P≤0.05), besides, barley based macaroni supplementation significantly improved the antioxidant status, which was achieved through the rise of serum Total Antioxidant Capacity and the decline of Malondialdehyde and Glutathione S-transferase activity (P≤0.05). Conclusion Barley-based prepared macaroni enriched with curcumin and ginger must be considered in alleviating the severity of knee OA symptoms to aid patients in getting their life back to near normal.